Immobilization Of β-Galactosidase Onto Activated Chitosan Support By Using Covalent Binding Method - Sezale, Nur Syahirah (Universiti Sains Malaysia, 2018)
The performance of immobilized β-galactosidase (β-Gal) onto chitosan support was studied in a batch process. The chitosan support was activated by using chemical agent which was glutaraldehyde solution. The main objective of this research was to investigate the suitable conditions in preparation of β-Gal immobilization process that will produce greater β-Gal activity. During the preparation of immobilized β-Gal, the optimum conditions were obtained from Response Surface Methodology (RSM). The optimum conditions were found to be 2% and 10 mg/ml for glutaraldehyde and β-Gal concentrations, respectively, which has resulted in 65.52% for activity yield meanwhile for immobilization yield, is 94.57%. The experimental results for investigation of effect of temperature on β-Gal activity, found that the optimum temperature at ℃ was obtained after β-Gal immobilization. However, it is so interesting that the immobilized β-Gal showed much better operational stability referring to a broader thermal range as compared to free β-Gal. The activity of immobilized β-Gal increased at about more than 17% of its initial activity, meanwhile the activity of free β-Gal reduced at less than 15%. Higher stability of β-Gal will lead to a better reusability. The immobilized β-Gal can be reused for six cycles and retained approximately 50% of its initial activity.